Unripe Papaya By-Product: From Food Wastes to Functional Ingredients in Pancakes - Waralee Joymak; Sathaporn Ngamukote; Praew Chantarasinlapin; Sirichai Adisakwattana (Foods, 2021)
Papaya is one of the most economic and valuable fruits in tropical countries. However, the fruit processing industries generate a high volume of unripe papaya waste and by-products. To reduce this waste, unripe papaya powder (UPP) was manufactured and incorporated into pancake formulation. The results showed that a particle size of UPP was 140.8 ± 2.1 µm, which contained polyphenolic compounds, dietary fiber and demonstrated ferric reducing antioxidant power (FRAP). Compared with wheat flour, UPP had higher values of water absorption index, water solubility index and swelling index and lower level of amylose. In the cholesterol-reducing effect, UPP decreased the formation of cholesterol micellization and bound bile acids. Interestingly, incorporation of 5–20% UPP into pancakes could decrease the glucose release with a concomitant increase in the percentage of undigestible starch. The hardness and chewiness of pancake was increased with a higher amount of UPP (10–20%). The results suggest that UPP from fruit processing waste can be regarded as a promising functional ingredient to incorporate with pancakes.